2017
DOI: 10.1016/j.psychres.2017.05.034
|View full text |Cite
|
Sign up to set email alerts
|

Is adolescent alcohol use associated with self-reported hypomanic symptoms in adulthood? – Findings from a prospective birth cohort

Abstract: High rates of alcohol use disorder (AUD) are reported in people with major depression (MD) and bipolar disorder (BD). Substance abuse problems in adolescence may also indicate risk for future onset of mood disorders, especially BD. Data collected from the Avon Longitudinal Study of Parents and Children (ALSPAC), a large UK birth cohort, allowed information to be collected over several different time points and to test whether problematic alcohol use at age 16 was predictive of vulnerability to hypomanic sympto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 43 publications
0
2
0
Order By: Relevance
“…This prevalence of binge alcohol drinking occurs at a critical period during development when the central nervous system is undergoing rapid adaptations in structure and function that could lead to vulnerability to mental disorders, such as anxiety. Epidemiological studies have shown that insidious alcohol use in adolescence predicts a vulnerability to mood disorders in adulthood [4].…”
Section: Introductionmentioning
confidence: 99%
“…This prevalence of binge alcohol drinking occurs at a critical period during development when the central nervous system is undergoing rapid adaptations in structure and function that could lead to vulnerability to mental disorders, such as anxiety. Epidemiological studies have shown that insidious alcohol use in adolescence predicts a vulnerability to mood disorders in adulthood [4].…”
Section: Introductionmentioning
confidence: 99%
“…The remaining associations were aggregated into a more inclusive category relating to substance use and mental health. Two articles reported that higher levels of alcohol [50] and cannabis use [51] at ages 16-17 were positively associated with hypomanic symptoms at ages 22-23.…”
Section: Other Substance Use and Mental Healthmentioning
confidence: 99%
“…Interestingly, another study has suggested that the relationship between alcohol use and depression may be mediated by a specific measure of alcohol involvement, whereby problematic use (defined by adverse consequences of alcohol use), but not alcohol intake (defined by the level of alcohol consumption) predicted young adult MDD (Mason et al, 2008 ). Self-reported alcohol use in adolescence has also been prospectively associated with hypomanic/manic symptoms at age 23 (Fasteau et al, 2017 ); however, these results solely relied on self-reported alcohol intake and problematic use and will need to be confirmed in future studies with more robust designs. Although the neural basis for the association between adolescent alcohol use and mood disorders has been largely unexplored, AUD symptom severity in adolescents was associated with increased amygdala responses to emotional compared to neutral stimuli (Aloi et al, 2018 ).…”
Section: Alcoholmentioning
confidence: 99%